Glycine-Stabilized Zinc Gluconate has similar bioavailability than Zinc Sulfate in a zinc fortified probiotic food - Tesan, Fiorella Carla (2011)
Objective: In this study, we evaluated zinc gluconate stabilized with glycine (GZ) and sulfate (SZ) in fermented milk as vehicle. Zinc bioavailability was evaluated in an animal model (Sprague Dawley rats) for both zinc sources in the vehicle with a probiotic (Lactobacillus casei DN114001). Results: For growth parameters, higher weight gain and femur weight values were observed when probiotic and zinc were provided together, independent of the source (weight gain: SZ 81.4g±4.0g; GZ 81.8g±4.0g and 70.2g±12.5g without the probiotic; femur weight: SZ 0.51g ±0.05g; GZ 0.52g±0.05g and 0.42g±0.03g without the probiotic). Femur zinc content was higher for zinc gluconate stabilized with glycine in the presence of the probiotic (97.04ppm±8.40ppm), and the results were similar for zinc sulfate with or without probiotic (84.51ppm±2.44ppm and 84.94ppm±2.28ppm, respectively). Serum antioxidant capacity and immune cellular response were also evaluated by using free radical scavenging assays and a T cell proliferation assay respectively. The free radical scavenging assay showed a tendency to increase with zinc provision, and the highest proliferation index was observed for glycine-stabilized zinc gluconate and the probiotic. Conclusion: The results indicate that the combination of zinc (as glycine-stabilized zinc gluconate) and a probiotic may be beneficial for the evaluated parameters.